POLA KOMUNIKASI KELUARGA BERCERAI DALAM PEMBENTUKAN KONSEP DIRI ANAK - Bethania Swasti Akmarani; Triyono Lukmantoro; Lintang Ratri Rahmiaji (Interaksi Online, 2023)
The impact of family divorce is felt by parents and children, including loss of emotional support, the emergence of conflict, and changes in aspects of the family. Post-divorce conflict and negative interactions between parents that are exposed to the child's daily life can reflect negative expressions and emotions in the family, while interactions around the child can be internalized and shape how the child sees themselves (self-concept). This research was conducted to find out how communication patterns within the family influence the formation of children's self-concept. The theories used in this research are family communication pattern theory and social self-construction theory. The method used in this research is descriptive qualitative with a phenomenological approach. The subjects in this study were children from divorced families who lived with one parent aged 15-21 years. The research results showed that one informant adhered to a consensual family communication pattern and two informants adhered to a protective family communication pattern. Both family communication patterns have a high conformity orientation, so that children are the ones who adapt and obey the parents' wishes, opinions and regulations. Furthermore, the results of this research also show that the formation of the informants' self-concept tends to be negative, characterized by low self-esteem, caused by the habit of comparing themselves with those around them, children see themselves as not comparable or equal to other people. Associated with a negative self-image from their own interpretation and evaluation, shown by a pessimistic and insecure attitude.